The coming Prince the marvellous prophecy of Daniel's seventy weeks concerning the antichrist - Anderson, Robert, 1841-1918 (Grand Rapids, MI Kregel, 1957)
Includes bibliographical references, index and chart.
Brethren writer. Donated by Mr A. Meers, student 1964-65.
Keywords: Bible. O.T. Daniel Apocalyptic passages -- criticism, interpretation, etc; Second advent; Antichrist